Ang bonggangbonggang batang beki The fierce and fabulous boy in pink! - Garlitos, Rhandee (Chikiting books, 2013)
"Adel seems to be different from the other boys his age. He is very fond of color pink which brings meaning to his life. But for his family and friends,, Adel is a son, sibling and friend that you will surely adore! Still, there are people who cannot easily accept Adel's identity and those like him. In one surprising instance,, Adel proves to everyone that true bravery and greatness do not lie in how one acts or looks, but in courage and self-acceptance."